Lithic miniaturization in South China since the terminal Pleistocene: A multivariate analysis of lithic reduction from Fodongdi, Fulin and Xiqiaoshan - Huan, Faxiang; Yang, Shixia; Marwick, Ben; Yu, Yanyan; Yue, Jianping; Pei, Shuwen; Petraglia, Michael (Journal of geographical sciences, 2025)
Lithic miniaturization is a key adaptive and technological feature of human populations and one of the key cultural hallmarks in the Late Pleistocene of Eastern Asia. In northern China this form of stone tool technology is well represented, including by microblade technology. Lithic miniaturization has been identified in South China, though this technological feature has received little research attention in comparison to the north. Here, we examine three miniaturized lithic assemblages in South China, ranging from the terminal Pleistocene to middle Holocene. To examine technological variations in lithic miniaturization, the three assemblages were subject to comparative quantitative analyses, including principal component analysis (PCA), K-means clustering and the Zingg system. The three sites were found to exhibit varied temporal and geographic patterns of lithic miniaturization across South China, potentially related to fluctuating climatic conditions and changes in population dynamics since the Late Pleistocene.